Intention to use PrEP among men who have sex with men and engage in chemsex - Sousa, Álvaro Francisco Lopes de (2023)
Funding Information: The authors disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: National Research Council – CNPq. Process: 159908/2019-1. Publisher Copyright: © The Author(s), 2023.